Correlation between Environmental and Individual Factors with Dermatitis Contact on Tobacco Farmers - Ike Puspitasari singgih Putri; Tri Martiana; Firman Suryadi Rahman (The Indonesian Journal of Occupational Safety and Health, 2020)
Introduction: Contact dermatitis is inflammation caused by substance which attaches to the skin. This contact dermatitis is divided into two, which are irritant contact dermatitis and allergic contact dermatitis. The purpose of this study was to analyze the factors associated with the incidence of contact dermatitis that occurred in translucent farmers in Ambulu village, Ambulu District, Jember district. Methods: The type of this research was observational analytic research with a cross-sectional approach. The population in this study was 61 tobacco farmers of ambulu village, taken by simple random sampling technique to obtain 53 tobacco farmers. The independent variables in this study were tenure, the frequency of contact, the duration of contact and age. The dependent variable was contact dermatitis. The test used to determine whether there was a relationship was the Chi-Square test. The results of this study were the results of frequency analysis of tobacco farmer contacts having a p-value of 0.020 smaller than 0.05 it is means that there was a relationship. The duration of contact p-value of 0.000 smaller than 0.05 so that there was a relationship between contact time and contact dermatitis. For the work period variables, there was not a relationship with contact dermatitis with p-value 0.210 greater than 0.05, while for the results of the age analysis obtained a p-value of 0.455 so that there was no relationship between over and contact dermatitis. Conclusion: There is a relationship between the frequency of contact and the duration of contact with contact dermatitis whereas for the working period and age there is no relationship with contact dermatitis Keywords: contact dermatitis, tobacco farmers